ATTENDANCE MANAGEMENT SYSTEM USING FINGERPRINT AND IRIS BIOMETRIC (FUDMA JOURNAL OF SCIENCES, 2023)
An attendance management system is a biometric system used in recording and managing attendance in higher institutions. Several methods of attendance management system has been developed mostly using a single factor. This paper presents an attendance management system which employs fingerprint and iris biometrics technique to record, monitor and manages student attendance. The system consists of a user interface, database, fingerprint and iris scanner installed at the entrance of lecture theatre. When student gets to the vicinity, he/she either present fingerprint or look directly towards the iris scanner. The scanner read the fingerprint/iris to get the pattern and compare it with the stored features in the attendance management system database, and displays successful if fingerprint/iris is verified else display the error “place fingerprint again for verification”. The system record, monitor and reports attendance of students on daily, weekly and monthly basis. It can also calculate 75% attendance of the student
Keywords: Attendance, Biometric, Fingerprint, Iris, Template